CRITICAL RECEPTION OF ALBERTO HIDALGO’S POETRY - Camacho Fuentes, Brenda (2012)
The purpose of this article, which is part of the author’s further work, refers to the reviewing studies and critical assessments of Alberto Hidalgo‘s poetry in the context of the development of the avant-garde, discussing the exegesis made by José Carlos Mariátegui and Estuardo Núñez, as well as the subsequent critical assessment of the process of emergence, settlement and development of the new poetry in Peru.